Metabolite Regulatory Interactions Control Plant Respiratory Metabolism via Target of Rapamycin (TOR) Kinase Activation - O’Leary, Brendan M. (Plant Cell, 2020)
Respiration rate measurements provide an important readout of energy expenditure and mitochondrial activity in plant cells during the night. As plants inhabit a changing environment, regulatory mechanisms must ensure that respiratory metabolism rapidly and effectively adjusts to the metabolic and environmental conditions of the cell. Using a high-throughput approach, we have directly identified specific metabolites that exert transcriptional, translational, and posttranslational control over the nighttime O(2) consumption rate (R(N)) in mature leaves of Arabidopsis (Arabidopsis thaliana). Multi-hour R(N) measurements following leaf disc exposure to a wide array of primary carbon metabolites (carbohydrates, amino acids, and organic acids) identified phosphoenolpyruvate (PEP), Pro, and Ala as the most potent stimulators of plant leaf R(N). Using metabolite combinations, we discovered metabolite-metabolite regulatory interactions controlling R(N). Many amino acids, as well as Glc analogs, were found to potently inhibit the R(N) stimulation by Pro and Ala but not PEP. The inhibitory effects of amino acids on Pro- and Ala-stimulated R(N) were mitigated by inhibition of the Target of Rapamycin (TOR) kinase signaling pathway. Supporting the involvement of TOR, these inhibitory amino acids were also shown to be activators of TOR kinase. This work provides direct evidence that the TOR signaling pathway in plants responds to amino acid levels by eliciting regulatory effects on respiratory energy metabolism at night, uniting a hallmark mechanism of TOR regulation across eukaryotes.